Postnatal Ontogenesis of the Islet Circadian Clock Plays a Contributory Role in β-Cell Maturation Process - Rakshit, Kuntol (Diabetes, 2018)
Development of cell replacement therapies in diabetes requires understanding of the molecular underpinnings of β-cell maturation. The circadian clock regulates diverse cellular functions important for regulation of β-cell function and turnover. However, postnatal ontogenesis of the islet circadian clock and its potential role in β-cell maturation remain unknown. To address this, we studied wild-type Sprague-Dawley as well as Period1 luciferase transgenic (Per1:LUC) rats to determine circadian clock function, clock protein expression, and diurnal insulin secretion during islet development and maturation process. We additionally studied β-cell–specific Bmal1-deficient mice to elucidate a potential role of this key circadian transcription factor in β-cell functional and transcriptional maturation. We report that emergence of the islet circadian clock 1) occurs during the early postnatal period, 2) depends on the establishment of global behavioral circadian rhythms, and 3) leads to the induction of diurnal insulin secretion and gene expression. Islet cell maturation was also characterized by induction in the expression of circadian transcription factor BMAL1, deletion of which altered postnatal development of glucose-stimulated insulin secretion and the associated transcriptional network. Postnatal development of the islet circadian clock contributes to early-life β-cell maturation and should be considered for optimal design of future β-cell replacement strategies in diabetes.